Programmed Cell Death in Sepsis Associated Acute Kidney Injury - Wu, Zhifen; Deng, Junhui; Zhou, Hongwen; Tan, Wei; Lin, Lirong; Yang, Jurong (Frontiers in Medicine, 2022)
Sepsis-associated acute kidney injury (SA-AKI) is common in patients with severe sepsis, and has a high incidence rate and high mortality rate in ICU patients. Most patients progress to AKI before drug treatment is initiated. Early studies suggest that the main mechanism of SA-AKI is that sepsis leads to vasodilation, hypotension and shock, resulting in insufficient renal blood perfusion, finally leading to renal tubular cell ischemia and necrosis. Research results in recent years have shown that programmed cell death such as apoptosis, necroptosis, pyroptosis and autophagy play important roles. In the early stage of sepsis-related AKI, autophagy bodies form and inhibit various types of programmed cell death. With the progress of disease, programmed cell death begins. Apoptosis promoter represents caspase-8-induced apoptosis and apoptosis effector represents caspase-3-induced apoptosis, however, caspase-11 and caspase-1 regulate gasdermin D-mediated pyroptosis. Caspase-8 and receptor interacting kinase 1 bodies mediate necroptosis. This review focuses on the pathophysiological mechanisms of various programmed cell death in sepsis-related AKI.